VO #034 Supply installation, testing & commissioning of ESE lighting protection system (rev.00) - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding VO #034 supply installation, testing & commissioning of ESE lighting protection system (rev.00) of BRAC University new campus project.